Pengaruh Pengadaan Beras dan Operasi Pasar Oleh Perum Bulog Terhadap Stabilitas Harga Beras di Provinsi Aceh - Fakulta, Fakulta; Juliansyah, Rollis (Universitas Teuku Umar, 2024)
The rice commodity plays an important role as a staple food product throughout the world, especially in Indonesia where the majority of the population consumes rice. This research aims to analyze the influence of rice procurement and operations carried out by Perum Bulog on the stability of rice prices in Aceh Province. The scope of this research is the Aceh province Bulog company which consists of 23 districts/cities. This research data uses quantitative data in the form of annual data. Data collection observations began in 2013 until 2022. The data used as the basis for this research is secondary data obtained from the Aceh Province BPS publication entitled Aceh in Figures in various editions. The analytical model used in this research is multiple linear regression. Procurement of rice is an important part of maintaining food security and ensuring the availability of sufficient staple food for the community. The amount of rice supply for market operations is also influenced by the large stock of rice available in the Government Rice Reserve (CBP) which is managed by Perum Bulog. The research results show that rice procurement and market operations have a significant influence on rice price stability and the success of the Government, in this case Perum Bulog, in maintaining price stability. This research proves that Bulog plays an effective role in maintaining rice price stability through rice procurement policies and market operations.